THE OCCURRENCE AND EXISTENCE OF SOCIAL CAPITAL IN COMMUNITY BAN HUAAEO DISTRICT SAM PHRAN NAKHON PATHOM - มะลินิน, วาสนา (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2019)
This research study based on the methodologies of qualitative research purposed for : 1. to study the occurrence and existence of social capital in community. 2. to study process and condition of the occurrence and existence of social capital by choosing study learning center of Ban Huaaeo District, Samphran Nakhonpathom with disabilities. Key informants, familial ties, kinship, seniority, villagers and leders of local. Research instruments are none-structured interview dual with field note. Researcher is using Documentary Analysis, Participation observation and In-depth interview. The results of this research that social capital in Ban Huaaeo communities of available social capital, cultural, natural resources, individual, group/organizational, kinship and network-based. The occurrence and existence of social capital in community activities were transfers of will aneesters had determined to keep going all forms of available community social capital and pass on to the new generations knowledge gained and accurnulated by the learned and experienced elderly both to keep and continue ; good/quality management process which relied on honest and hard-working individuals in carrying out various group activities. Both leaders and each member were seen as crucial actors in conducting and sustaining group activities. Such process depended on dedication and participation of all which lead to group power, fair distribution of financial interests and equal share of physical labour. Futhermore, group/organizational rules and requlations were both accepted and observed by every member ; leaders, having good, visionary, and responsible leaders capable of leading various activities. At the same time, having good followers also helped a great deal. The cooperated and were united in completing the tasks at hand, networks, internally and externally estaldished networks working to connect with outside networked organizations in order to strengthen community ones relying as much as possible on themselves